Catalytic carbonized flame-retardant polyolefin nano composite material as well as preparation process and application thereof
By using a metal organic frame MOFs-supported dual catalyst technology in polyolefin materials, the staged temperature response mechanism and the formation of a carbonized layer are achieved, which solves the shortcomings of the flame retardant mechanism and preparation process in the prior art, and significantly improves the flame retardant performance and mechanical properties.
Patent Information
- Application Number
- CN202510146109.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-10
- Publication Date
- 2025-04-11
AI Technical Summary
The existing polyolefin flame retardant technology has a single catalytic mechanism that is difficult to play a comprehensive and effective role in different fire stages, and traditional processes are difficult to achieve uniform dispersion of nanomaterials in polyolefin matrix, resulting in unstable performance.
Metal-organic frame MOFs are used as nanoreactors, and in-situ supported aluminum hypophosphate and transition metal nickel dual catalysts are realized to achieve a staged temperature response mechanism of crosslinking-carbonization-free radical quenching, forming a dense carbonization layer and honeycomb aerogel structure.
The flame retardant performance of the material is significantly improved, and the triple-repellent flame retardant effect of "physical barrier-chemical quenching-pyrolytic gas dilution" is achieved, while maintaining the good mechanical properties of the polyolefin material.
Smart Images

Figure CN119798826A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of polymer flame retardant materials, in particular to a catalytic carbonization flame retardant polyolefin nanocomposite material and a preparation process and application thereof. Background Art
[0002] With the rapid development of modern industrial technology, polymer materials have been widely used in many fields such as wires and cables, building materials, plastic products, etc. due to their excellent physical, chemical properties and processing properties. However, polymer materials tend to release toxic and harmful gases when burned, causing safety hazards. Therefore, the development of polymer materials with high-efficiency flame retardant properties has become one of the important directions of current material science research. Catalytic carbonization flame retardant technology, as a new flame retardant method, introduces specific catalysts to promote the carbonization reaction of polymer materials at high temperature to form a dense carbon layer, thereby effectively isolating oxygen and heat transfer and improving the flame retardant properties of the material.
[0003] At present, the existing polyolefin flame retardant technology has many drawbacks. In terms of flame retardant mechanism, the existing technology adopts a single catalytic mechanism, which is difficult to play a comprehensive and effective flame retardant role in different fire stages. For example, in the early stage of a fire, it is impossible to quickly form an effective physical barrier to prevent the spread of the fire; in the development stage of the fire, chemical quenching and pyrolysis gas dilution cannot be carried out efficiently; in terms of material preparation technology, traditional methods are difficult to achieve uniform dispersion of nanomaterials in the polyolefin matrix, resulting in unstable performance of the composite material, and the conventional catalyst loading method cannot accurately control the distribution of the catalyst, affecting the catalytic efficiency and flame retardant effect; in addition, the flame retardant polyolefin materials prepared by the existing technology often require the addition of a large amount of flame retardants, which seriously damages the original mechanical properties and processing properties of the material, limiting its practical application; In summary, it is urgent to develop a polyolefin nanocomposite material and its preparation process with high-efficiency flame retardant properties, good mechanical properties and stable structure. This new material and process must not only overcome the defects of the existing technology in flame retardant mechanism and preparation process, but also meet the strict requirements of different industries on material properties, and provide possibilities for the safe application of polyolefin materials in more fields. Summary of the invention
[0004] The purpose of the present invention is to make up for the deficiencies of the prior art and provide a catalytic carbonization flame-retardant polyolefin nanocomposite material and a preparation process and application thereof. The present invention can realize a staged temperature response mechanism of crosslinking-carbonization-free radical quenching by adopting metal organic frameworks MOFs as nanoreactors and in-situ loading aluminum hypophosphite and transition metal nickel dual catalysts in the pores thereof. During the combustion process of the polyolefin material, the system can efficiently catalyze the carbonization reaction to form a dense carbonization layer, effectively preventing the transfer of heat and oxygen, thereby significantly improving the flame retardant properties of the material. In addition, the acidic gas released by the composite material during the combustion process can directionally etch the MOFs shell and synchronously release the PO· free radical scavenger, further improving the flame retardant properties of the material, and realizing the triple combination of "physical barrier-chemical quenching-pyrolysis gas dilution".
[0005] In order to solve the above technical problems, the present invention provides the following technical solutions: On the one hand, a catalytic carbonization flame-retardant polyolefin nanocomposite material, the components of the composite material include: a polyolefin matrix, a metal organic framework, aluminum hypophosphite, transition metal nickel, and thiol and olefin monomers for dynamic thiol-ene click reaction; The metal organic framework is a zirconium phosphate core-shell structure, which serves as a nanoreactor, and in-situ loads aluminum hypophosphite and transition metal nickel dual catalysts in its pores; The aluminum hypophosphite is used as a high-temperature pyrolysis catalyst, which pyrolyzes at above 300°C to release acidic gas to directionally etch the metal organic framework shell, and simultaneously releases PO· free radical scavenger to reduce the heat release rate during material combustion; The transition metal nickel ions are used as low-temperature cross-linking catalysts to trigger the polyolefin pre-cross-linking reaction, triggering the polyolefin pre-cross-linking to form a three-dimensional network at 200-250°C; The thiol and ene monomers introduce a dynamic thiol-ene click reaction to control the degree of crosslinking; The polyolefin matrix uses polyethylene as a basic material, accounting for 70-85% of the total weight of the composite material, and is used to carry other components and jointly construct a nanocomposite material system with catalytic carbonization and flame retardant functions.
[0006] Furthermore, the core-shell structure MOFs nanoreactor accounts for 5-15% of the total mass of the composite material, the aluminum hypophosphite catalyst is loaded on the outer surface of the MOFs nanoreactor, accounting for 2-8% of the total mass of the composite material, and the transition metal nickel catalyst is loaded on the inner surface of the MOFs nanoreactor, accounting for 0.5-3% of the total mass of the composite material.
[0007] Furthermore, the total amount of the thiol and olefin monomers used for the dynamic thiol-ene click reaction accounts for 1-5% of the total mass of the composite material, wherein the molar ratio of the thiol to the olefin monomer is 0.8-1.2:1.
[0008] On the other hand, a process for preparing a catalytic carbonization flame-retardant polyolefin nanocomposite material, the specific steps of the composite material preparation process are: S100, preparing a metal organic framework MOFs nanoreactor: introducing a zinc salt and a 2-methylimidazole precursor solution into the first section of a twin-screw extruder, synthesizing ZIF-8 in a polyolefin matrix, mixing ZIF-8 with a zirconium phosphate solution, coating the surface of ZIF-8 with zirconium phosphate, and forming a MOFs nanoreactor with a zirconium phosphate core-shell structure; S200, loading dual catalysts: in the second section of the twin-screw extruder, the synthesized MOFs nanoreactor is dispersed in a mixed solution of aluminum hypophosphite and transition metal nickel salt, and the aluminum hypophosphite is loaded on the outer surface of the MOFs nanoreactor and the transition metal nickel is loaded on the inner surface of the MOFs nanoreactor by adsorption-impregnation, thereby forming a MOFs nanoreactor loaded with dual catalysts; S300, mixing a polyolefin matrix: uniformly mixing the polyolefin matrix with additives and fillers to form a polyolefin matrix mixture; S400, introducing a dynamic thiol-ene click reaction: mixing thiol and olefin monomers, adding the mixture to a polyolefin matrix mixture, and uniformly dispersing the thiol and olefin monomers in the polyolefin matrix by stirring to form a mixture containing a dynamic thiol-ene click reaction system; S500, reactive extrusion: extruding and mixing a mixture containing a MOFs nanoreactor and a dynamic thiol-ene click reaction system through the third section of a twin-screw extruder. During the extrusion process, the components are fully mixed and uniformly mixed through the shearing and mixing action of the screw. Meanwhile, the dynamic thiol-ene click reaction reacts during the extrusion process to form a pre-crosslinked network structure. S600, microwave curing: the extruded mixture is cured, and under the action of microwaves, a local temperature gradient is induced in the material to form a flame retardant gradient structure; S700, post-processing: performing post-processing operations of cooling and cutting the cured composite material to obtain a final catalytic carbonization flame-retardant polyolefin nanocomposite material.
[0009] Furthermore, the temperature of the first section of the S100 twin-screw extruder is 80-120°C, and during the synthesis of ZIF-8 in a polyolefin matrix, an ultrasound-assisted micro-reaction technology with a frequency of 40kHz and a power density of 0.5W / cm² is turned on.
[0010] Furthermore, the temperature of the second section of the S200 twin-screw extruder is 150-180°C, and an aluminum hypophosphite / nickel salt mixed solution is injected to achieve selective loading by utilizing the molecular sieve effect of the MOFs pores. By adjusting the pH value of the system to 5.5-6.0, nickel ions are preferentially adsorbed on the inner surface of MOFs, and aluminum hypophosphite is distributed on the outer surface, forming a gradient distribution structure.
[0011] Furthermore, the temperature of the third section of the S500 twin-screw extruder is 200-220°C, thiol and olefin monomers are introduced, and the alternating distribution of high shear zone and low shear zone is achieved by making the kneading block angle 45° and the gap 0.5mm, and the crosslinking degree is controlled at 15-25%.
[0012] Furthermore, the S600 microwave frequency is 2.45 GHz, the power density is 2-3 W / g, and the processing time is 1-5 minutes.
[0013] Furthermore, a catalytic carbonization flame-retardant polyolefin nanocomposite material is used in the preparation of flame-retardant wires and cables, flame-retardant building materials and flame-retardant plastic products.
[0014] Compared with the prior art, the catalytic carbonization flame-retardant polyolefin nanocomposite material and its preparation process and application have the following beneficial effects: 1. The catalytic carbonization flame-retardant polyolefin nanocomposite material of the present invention realizes the triple composite flame retardant effect of "physical barrier-chemical quenching-pyrolysis gas dilution" through a gradient catalysis-carbonization bifunctional MOFs system. When a fire occurs, the staged catalytic mechanism can accurately respond to different temperature stages. At 200-250°C, nickel ions trigger polyolefin pre-crosslinking to form a three-dimensional network to construct a physical barrier. Above 300°C, aluminum hypophosphite is pyrolyzed to release acidic gas to etch the MOFs shell and release free radical scavengers, thereby performing chemical quenching and pyrolysis gas dilution. At the same time, the honeycomb aerogel structure formed inside the carbonization layer further enhances the flame retardant effect and maintains the good mechanical properties of the polyolefin material, so that it can function stably in various application scenarios.
[0015] 2. In terms of preparation technology, the integrated process of MOFs in-situ growth-confined loading and the collaborative processing technology of reaction extrusion-microwave curing ensure the stability of the material structure and the consistency of performance. The in-situ growth of MOFs accurately controls the size and dispersibility of nanomaterials, and the confined loading realizes the gradient distribution of catalysts and improves the catalytic efficiency. The "rigid outside and soft inside" flame-retardant gradient structure formed by the collaborative technology of reaction extrusion-microwave curing makes the material surface hard and wear-resistant, and the internal flexibility is strong and the impact resistance is excellent, ensuring the reliability and safety of the material in long-term use.
[0016] Other advantages, objectives and features of the present invention will be set forth in part in the following description and, in part, will be apparent to those skilled in the art based on an examination of the following or may be taught from the practice of the present invention. BRIEF DESCRIPTION OF THE DRAWINGS
[0017] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the prior art descriptions are briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention, and for ordinary technicians in this field, other drawings can be obtained based on these drawings without creative work.
[0018] Figure 1 The present invention is a flow chart of a preparation process of a catalytic carbonization flame-retardant polyolefin nanocomposite material. DETAILED DESCRIPTION
[0019] In order to further explain the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation mode, structure, characteristics and effects of the present invention are described in detail below in combination with the accompanying drawings and preferred embodiments.
[0020] A catalytic carbonization flame-retardant polyolefin nanocomposite material, the components of which include: a polyolefin matrix, a metal organic framework, aluminum hypophosphite, transition metal nickel, and thiol and olefin monomers for a dynamic thiol-ene click reaction; The metal organic framework is a zirconium phosphate core-shell structure, which serves as a nanoreactor and accounts for 5-15% of the total mass of the composite material. The pores of the metal organic framework are in-situ loaded with aluminum hypophosphite and transition metal nickel dual catalysts, wherein the aluminum hypophosphite catalyst is loaded on the outer surface of the MOFs nanoreactor and accounts for 2-8% of the total mass of the composite material, and the transition metal nickel catalyst is loaded on the inner surface of the MOFs nanoreactor and accounts for 0.5-3% of the total mass of the composite material; The aluminum hypophosphite is used as a high-temperature pyrolysis catalyst, which pyrolyzes at above 300°C to release acidic gas to directionally etch the metal organic framework shell, and simultaneously releases PO· free radical scavenger to reduce the heat release rate during material combustion; The transition metal nickel ions are used as low-temperature cross-linking catalysts to trigger the polyolefin pre-cross-linking reaction, triggering the polyolefin pre-cross-linking to form a three-dimensional network at 200-250°C; The thiol and olefin monomers introduce a dynamic thiol-ene click reaction to control the degree of crosslinking, and the total amount of the two accounts for 1-5% of the total mass of the composite material, wherein the molar ratio of thiol to olefin monomer is 0.8-1.2:1; The polyolefin matrix uses polyethylene as a basic material, accounting for 70-85% of the total weight of the composite material, and is used to carry other components and jointly construct a nanocomposite material system with catalytic carbonization and flame retardant functions.
[0021] like Figure 1 As shown, the specific steps of the preparation process of the composite material are: S100, preparation of metal organic framework MOFs nanoreactor: in the first section of the twin-screw extruder, the temperature is set to 80-120°C, zinc salt and 2-methylimidazole precursor solution are introduced to synthesize ZIF-8 in a polyolefin matrix, and in the process of synthesizing ZIF-8 in the polyolefin matrix, an ultrasonic-assisted micro-reaction technology with a frequency of 40kHz and a power density of 0.5W / cm² is turned on to mix ZIF-8 with a zirconium phosphate solution, and zirconium phosphate is coated on the surface of ZIF-8 to form a MOFs nanoreactor with a zirconium phosphate core-shell structure; S200, loading dual catalysts: in the second section of the twin-screw extruder, the temperature is adjusted to 150-180° C., the synthesized MOFs nanoreactor is dispersed in a mixed solution of aluminum hypophosphite and transition metal nickel salt, and the aluminum hypophosphite is loaded on the outer surface of the MOFs nanoreactor and the transition metal nickel is loaded on the inner surface of the MOFs nanoreactor by adjusting the pH value of the system to 5.5-6.0, so as to form a gradient structure MOFs nanoreactor loaded with dual catalysts; S300, mixing a polyolefin matrix: uniformly mixing the polyolefin matrix with additives and fillers to form a polyolefin matrix mixture; S400, introducing a dynamic thiol-ene click reaction: mixing thiol and olefin monomers, adding the mixture to a polyolefin matrix mixture, and uniformly dispersing the thiol and olefin monomers in the polyolefin matrix by stirring to form a mixture containing a dynamic thiol-ene click reaction system; S500, reactive extrusion: extruding and mixing a mixture containing a MOFs nanoreactor and a dynamic thiol-ene click reaction system through the third section of a twin-screw extruder, wherein the temperature of the third section is 200-220° C., introducing thiol and olefin monomers during the extrusion process, making the kneading block angle 45° and the gap 0.5 mm, achieving alternating distribution of high shear zone and low shear zone, and controlling the crosslinking degree at 15-25%, and fully mixing the components through the shearing and mixing action of the screw, and at the same time, the dynamic thiol-ene click reaction reacts during the extrusion process to form a pre-crosslinked network structure; S600, microwave curing: the extruded mixture is cured, the microwave frequency is set to 2.45GHz, the power density is 2-3W / g, and the treatment time is 1-5 minutes. Under the action of microwaves, the material is induced to produce a local temperature gradient to form a flame retardant gradient structure; S700, post-processing: performing post-processing operations of cooling and cutting the cured composite material to obtain a final catalytic carbonization flame-retardant polyolefin nanocomposite material.
[0022] Embodiment 1
[0023] Raw material preparation stage: accurately weigh 70g of high-purity polyethylene particles as the polyolefin matrix, with a purity of more than 99.5% to ensure the stable performance of the basic material, prepare 5g of analytically pure zinc salt and 8g of 2-methylimidazole with a purity of 98% for the synthesis of ZIF-8, select 3g of aluminum hypophosphite and 1g of transition metal nickel salt, both of which are chemically pure reagents, 1-octanethiol is selected as the thiol, and 1-hexene is selected as the olefin monomer, and accurately weigh them according to the molar ratio of 0.8:1, a total of 3g, at the same time, prepare a sufficient amount of analytically pure zirconium phosphate solution, as well as appropriate amounts of antioxidants, calcium carbonate fillers and other additives.
[0024] Preparation process: The temperature of the first section of the twin-screw extruder was set to 80°C, the ultrasound-assisted micro-reaction technology was turned on, the frequency was stabilized at 40kHz, and the power density was maintained at 0.5W / cm². Under this condition, the zinc salt and 2-methylimidazole precursor solution were slowly introduced into the polyolefin matrix, and the reaction lasted for 30 minutes to fully synthesize ZIF-8 in the polyolefin matrix. Subsequently, the synthesized ZIF-8 and zirconium phosphate solution were mixed in a volume ratio of 1:1.2, and stirred in a constant temperature water bath at 50°C for 2 hours to uniformly coat the zirconium phosphate on the surface of ZIF-8 to form a MOFs nanoreactor with a zirconium phosphate core-shell structure; in the second section of the twin-screw extruder, the temperature was adjusted to 150°C, and the synthesized MOFs nanoreactor was slowly dispersed in a mixed solution of aluminum hypophosphite and nickel salt, and the pH value of the system was accurately adjusted to 5.5 using a pH regulator. The adsorption-impregnation effect lasted for 4 hours to achieve the loading of aluminum hypophosphite on the outer surface and transition metal nickel on the inner surface, forming a MOFs nanoreactor loaded with dual catalysts; the polyolefin matrix was mixed with 0.5g of antioxidant and 5g of calcium carbonate filler in a high-speed mixer at a speed of 800r / min for 15 minutes to uniformly disperse it. , forming a polyolefin matrix mixture, then, adding the pre-weighed thiol and olefin monomers to the polyolefin matrix mixture, stirring for 30 minutes at a stirring speed of 600r / min to ensure that the monomers are evenly dispersed, and forming a mixture containing a dynamic thiol-ene click reaction system; sending the mixture containing the MOFs nanoreactor and the dynamic thiol-ene click reaction system into the third section of the twin-screw extruder, setting the temperature to 200°C, adjusting the screw configuration so that the kneading block angle is 45° and the gap is 0.5mm, continuing the reaction for 1 hour during the extrusion process, controlling the crosslinking degree at 15%, forming a pre-crosslinked network structure, finally, placing the extrudate in a microwave device, curing it at a microwave frequency of 2.45GHz and a power density of 2W / g for 1 minute, then naturally cooling it to room temperature, and cutting it into standard test strips.
[0025] Performance test and result analysis: The prepared composite material was subjected to a limiting oxygen index (LOI) test: by introducing a mixed gas of oxygen and nitrogen, the oxygen concentration was gradually increased until the sample could just maintain combustion, and the oxygen concentration at this time was recorded. The LOI value reached 35%; vertical combustion test: the sample was ignited with a Bunsen burner flame and then removed after 10 seconds to observe the combustion of the sample. During the combustion process, the material was able to quickly self-extinguish, and there was no phenomenon of burning drippings igniting the absorbent cotton, indicating that the material had good flame retardant properties; tensile strength and flexural strength tests: the tensile strength was 30MPa, and the flexural strength was 40MPa, indicating that the material had good mechanical properties under the conditions of lower temperature and less monomer dosage.
[0026] Embodiment 2
[0027] Raw material preparation: 75g of stable polyethylene was selected as the polyolefin matrix, the melt flow rate of the polyethylene was 2g / 10min (190℃, 2.16kg), 6g of zinc salt and 9g of 2-methylimidazole were weighed, both of which had a purity of more than 98%, 4g of aluminum hypophosphite and 1.5g of transition metal nickel salt were prepared. The thiol and olefin monomers were still 1-octanethiol and 1-hexene, and a total of 3.5g was accurately weighed according to the molar ratio of 1:1. At the same time, appropriate amounts of zirconium phosphate solution, ultraviolet absorber and talcum powder filler were prepared.
[0028] Preparation process: The temperature of the first section of the twin-screw extruder was set to 90°C, and the ultrasound-assisted micro-reaction technology (40kHz, 0.5W / cm²) was turned on. The zinc salt and 2-methylimidazole precursor solution were introduced and reacted for 35 minutes to synthesize ZIF-8, which was then mixed and stirred with the zirconium phosphate solution at 60°C for 2.5 hours to complete the preparation of the MOFs nanoreactor; the temperature of the second section was adjusted to 160°C, and the synthesized MOFs nanoreactor was dispersed in the mixed solution of aluminum hypophosphite and nickel salt. The pH value was adjusted to 5.7, and adsorption-impregnation was performed for 4.5 hours to achieve dual catalyst loading; when mixing the polyolefin matrix, polyethylene was mixed with 0.8g ultraviolet The absorbent UV-531 and 8 g of talcum powder filler were mixed in a high-speed mixer at a speed of 900 r / min for 20 minutes, and then thiol and olefin monomers were added, the stirring speed was maintained at 700 r / min, and the mixture was stirred for 35 minutes to form a mixture containing a dynamic thiol-ene click reaction system; the mixture entered the third section of the twin-screw extruder, the temperature was set to 210°C, the screw kneading block angle was adjusted to 45° and the gap was 0.5 mm, the extrusion reaction was carried out for 1.2 hours, and the crosslinking degree was controlled at 20%. Finally, the microwave curing conditions were set to a frequency of 2.45 GHz, a power density of 2.5 W / g, and a processing time of 2 minutes. After curing, it was cooled and cut into standard strips.
[0029] Performance test results: The LOI test results show that the LOI value is increased to 37%, the flame retardant performance is good in the vertical combustion test, the tensile strength test and the bending strength test, the tensile strength is 33MPa, and the bending strength reaches 43MPa, which shows that by appropriately increasing the temperature and monomer dosage, the comprehensive performance of the material has been effectively improved, and the mechanical properties have also been enhanced.
[0030] Embodiment 3
[0031] Raw material selection and preparation: Accurately weigh 80g of polyethylene, with a density of 0.93g / cm³. Use 7g of zinc nitrate as zinc salt and 10g of 2-methylimidazole, both with a purity of not less than 98%. Prepare 5g of aluminum hypophosphite, 2g of transition metal nickel salt, and 4g of 1-decyl mercaptan and 1-octene as thiol and olefin monomers at a molar ratio of 1.1:1. At the same time, prepare sufficient zirconium phosphate solution, toughening agent POE and mica powder filler.
[0032] Material preparation process: In the first section of the twin-screw extruder, the temperature was raised to 100°C, and the ultrasonic-assisted micro-reaction technology (40kHz, 0.5W / cm²) was started. Zinc salt and 2-methylimidazole precursor solution were added and reacted for 40 minutes to synthesize ZIF-8. Then, it was stirred with zirconium phosphate solution at 70°C for 3 hours to form a MOFs nanoreactor; the temperature of the second section was set to 170°C, and the MOFs nanoreactor was dispersed in a mixed solution of aluminum hypophosphite and nickel salt. The pH value was adjusted to 5.8, and after 5 hours of adsorption-impregnation, the dual catalyst loading was completed; polyethylene was mixed with 1.2g toughening agent POE and 10g mica powder filler in a high-speed mixer at a speed of 1000r / min for 25 minutes. Then add thiol and olefin monomers, stir at 800r / min for 40 minutes to form a mixture containing a dynamic thiol-ene click reaction system; the mixture enters the third section, the temperature is maintained at 215°C, the screw kneading block angle is 45°, the gap is 0.5mm, the extrusion reaction is 1.5 hours, and the crosslinking degree is controlled at 22%. Microwave curing uses a frequency of 2.45GHz and a power density of 2.8W / g for 3 minutes, and finally cooled and cut into standard strips.
[0033] Performance test results: LOI value reaches 38%, flame retardant performance is excellent, tensile strength is 35MPa, and flexural strength reaches 45MPa, indicating that under this parameter condition, the comprehensive performance of the material is further optimized, and the mechanical properties and flame retardant properties achieve a good balance.
[0034] Embodiment 4
[0035] Raw material preparation: Take 83g of polyethylene with good processing performance, with a melt flow rate of 3g / 10min (190℃, 2.16kg), prepare 8g of zinc salt and 11g of 2-methylimidazole, both with a purity of more than 98.5%. 6g of aluminum hypophosphite, 2.5g of transition metal nickel salt. The thiol and olefin monomers are 1-dodecanethiol and 1-decene, weighing a total of 4.5g at a molar ratio of 1.2:1, and prepare zirconium phosphate solution, antistatic agent SN and kaolin filler.
[0036] Preparation process implementation: The temperature of the first section of the twin-screw extruder was set to 110°C, and the ultrasound-assisted micro-reaction technology (40kHz, 0.5W / cm²) was turned on. The zinc salt and 2-methylimidazole precursor solution were introduced and reacted for 45 minutes to synthesize ZIF-8, and then stirred with the zirconium phosphate solution at 80°C for 3.5 hours to prepare the MOFs nanoreactor; the temperature of the second section was adjusted to 175°C, and the MOFs nanoreactor was dispersed in the mixed solution of aluminum hypophosphite and nickel salt, and the pH value was adjusted to 5.9 for 5.5 hours. Adsorption-impregnation to achieve dual catalyst loading; polyethylene, 1.5g antistatic agent SN, and 12g kaolin filler were mixed in a high-speed mixer at a speed of 1100r / min for 30 minutes, and then thiol and olefin monomers were added and stirred at a speed of 900r / min for 45 minutes to form a mixture containing a dynamic thiol-ene click reaction system; the mixture entered the third section, the temperature was set to 218℃, the screw kneading block angle was 45°, the gap was 0.5mm, the extrusion reaction was 1.8 hours, and the crosslinking degree was controlled at 23%. During microwave curing, the frequency was 2.45GHz, the power density was 2.9W / g, the treatment was 4 minutes, and finally cooled and cut into standard strips.
[0037] Performance test results: LOI value is close to 39%, flame retardant performance is excellent, tensile strength reaches 36MPa, and flexural strength is 46MPa, indicating that the material performance is good under this parameter.
[0038] Embodiment 5
[0039] Precise preparation of raw materials: weigh 85g high-density polyethylene with a density of 0.95g / cm³. 9g zinc salt, 12g 2-methylimidazole, both with a purity of 99%. 8g aluminum hypophosphite, 3g transition metal nickel salt, 5g of 1-tetradecapol and 1-dodecene, selected as thiol and olefin monomers, at a molar ratio of 1.2:1. At the same time, prepare appropriate amounts of zirconium phosphate solution, lubricant zinc stearate and bentonite filler.
[0040] Material preparation steps: The temperature of the first section of the twin-screw extruder was set to 120°C, and the ultrasound-assisted micro-reaction technology (40kHz, 0.5W / cm²) was turned on. Zinc salt and 2-methylimidazole precursor solution were introduced and reacted for 50 minutes to synthesize ZIF-8, which was then stirred with zirconium phosphate solution at 90°C for 4 hours to form a MOFs nanoreactor; the temperature of the second section was adjusted to 180°C, and the MOFs nanoreactor was dispersed in a mixed solution of aluminum hypophosphite and nickel salt, the pH value was adjusted to 6.0, and adsorption-impregnation was performed for 6 hours to complete the dual catalyst loading; polyethylene was mixed with 2g Lubricant zinc stearate and 15g bentonite filler are mixed in a high-speed mixer at a speed of 1200r / min for 35 minutes, and then thiol and olefin monomers are added, and stirred at a speed of 1000r / min for 50 minutes to form a mixture containing a dynamic thiol-ene click reaction system; the mixture enters the third section, the temperature is maintained at 220°C, the screw kneading block angle is 45°, the gap is 0.5mm, the extrusion reaction is carried out for 2 hours, the crosslinking degree is controlled at 25%, and the microwave curing adopts a frequency of 2.45GHz and a power density of 3W / g for 5 minutes, and the mixture is cooled and cut into standard strips.
[0041] Performance test results: LOI value is about 39.5%, flame retardant performance is excellent, tensile strength is 37MPa, bending strength is 47MPa, and material performance is good.
[0042] Comparative Example Raw material preparation: Weigh 70g of polyethylene, use 5g of traditional flame retardant decabromodiphenyl ether, and do not use metal organic frameworks, aluminum hypophosphite, transition metal nickel, and thiol and olefin monomers.
[0043] Operation steps: Mix polyethylene and decabromodiphenyl ether directly in a twin-screw extruder at an extrusion temperature of 180°C, and cool and cut after extrusion.
[0044] Performance test results: LOI value is only 28%, flame retardant performance is poor, self-extinguishing performance is poor, tensile strength is 20MPa, and flexural strength is 30MPa.
[0045] The specific data of the catalytic carbonization flame-retardant polyolefin nanocomposite materials provided in Examples 1 to 5 and Comparative Examples are shown in the following table:
[0046] As shown in the table above, by analyzing the performance test results of Examples 1 to 5 and the comparative example, it can be seen that the catalytic carbonization flame-retardant polyolefin nanocomposite prepared by the present invention exhibits significant advantages in flame retardancy and mechanical properties, among which: The flame retardant performance has obvious advantages: from the perspective of limiting oxygen index (LOI), the LOI values of Examples 1 to 5 gradually increase from 35% to about 39.5%, indicating that with the increase in the amount of raw materials used and the optimization of conditions such as the preparation temperature, the flame retardant performance of the material continues to increase. In comparison, the comparative example uses a traditional flame retardant, and the LOI value is only 28%, which is much lower than that of each example, highlighting the unique gradient catalysis-carbonization dual-functional MOFs system of the present invention in terms of flame retardancy. In the vertical combustion test, Examples 1 to 5 show excellent flame retardant performance, and there is no phenomenon of burning drippings igniting the absorbent cotton, while the comparative example is less effective in preventing material combustion and controlling the spread of fire. The composite material of the present invention can better meet the application scenarios with high flame retardant requirements; Simultaneous optimization of mechanical properties: The tensile strength of Examples 1 to 5 is increased from 30MPa to 37MPa, and the flexural strength is increased from 40MPa to 47MPa, showing a trend of gradual enhancement. This is due to the MOFs in-situ growth-confined loading integrated process and the collaborative processing technology of reactive extrusion-microwave curing. These processes ensure the stability of the material structure, so that the material has good flame retardant properties while the mechanical properties are effectively improved. In contrast, the tensile strength of the comparative example is only 20MPa, and the flexural strength is 30MPa. The large amount of traditional flame retardants added seriously damages the original mechanical properties of the material and limits its practical application.
[0047] In summary, the catalytic carbonization flame-retardant polyolefin nanocomposite material of the present invention realizes the triple composite flame retardant effect of "physical barrier-chemical quenching-pyrolysis gas dilution" through a unique gradient catalysis-carbonization bifunctional MOFs system. In addition, the formation of the honeycomb carbon layer effectively isolates heat and oxygen, further improves the flame retardant efficiency, and maintains the good mechanical properties of the polyolefin material, so that it can play a stable role in various application scenarios.
[0048] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A catalytic carbonization flame-retardant polyolefin nanocomposite material, characterized in that: The composite material comprises: a polyolefin matrix, a metal organic framework, aluminum hypophosphite, transition metal nickel, and thiol and ene monomers for a dynamic thiol-ene click reaction; The metal organic framework is a zirconium phosphate core-shell structure, which serves as a nanoreactor, and in-situ loads aluminum hypophosphite and transition metal nickel dual catalysts in its pores; The aluminum hypophosphite is used as a high-temperature pyrolysis catalyst, which pyrolyzes at above 300°C to release acidic gas to directionally etch the metal organic framework shell, and simultaneously releases PO· free radical scavenger to reduce the heat release rate during material combustion; The transition metal nickel ions are used as low-temperature cross-linking catalysts to trigger the polyolefin pre-cross-linking reaction, triggering the polyolefin pre-cross-linking to form a three-dimensional network at 200-250°C; The thiol and ene monomers introduce a dynamic thiol-ene click reaction to control the degree of crosslinking; The polyolefin matrix uses polyethylene as a basic material, accounting for 70-85% of the total weight of the composite material, and is used to carry other components and jointly construct a nanocomposite material system with catalytic carbonization flame retardant functions.
2. The catalytic carbonization flame-retardant polyolefin nanocomposite material according to claim 1, characterized in that: The core-shell structure MOFs nanoreactor accounts for 5-15% of the total mass of the composite material, the aluminum hypophosphite catalyst is loaded on the outer surface of the MOFs nanoreactor, accounting for 2-8% of the total mass of the composite material, and the transition metal nickel catalyst is loaded on the inner surface of the MOFs nanoreactor, accounting for 0.5-3% of the total mass of the composite material.
3. The catalytic carbonization flame-retardant polyolefin nanocomposite material according to claim 1, characterized in that: The total amount of the thiol and olefin monomers used for the dynamic thiol-ene click reaction accounts for 1-5% of the total mass of the composite material, wherein the molar ratio of the thiol to the olefin monomer is 0.8-1.2:
1.
4. A process for preparing a catalytic carbonization flame-retardant polyolefin nanocomposite material, applicable to a catalytic carbonization flame-retardant polyolefin nanocomposite material as claimed in any one of claims 1 to 3, characterized in that: The specific steps of the composite material preparation process are: S100, preparing a metal organic framework MOFs nanoreactor: introducing a zinc salt and a 2-methylimidazole precursor solution into the first section of a twin-screw extruder, synthesizing ZIF-8 in a polyolefin matrix, mixing ZIF-8 with a zirconium phosphate solution, coating the surface of ZIF-8 with zirconium phosphate, and forming a MOFs nanoreactor with a zirconium phosphate core-shell structure; S200, loading dual catalysts: in the second section of the twin-screw extruder, the synthesized MOFs nanoreactor is dispersed in a mixed solution of aluminum hypophosphite and transition metal nickel salt, and the aluminum hypophosphite is loaded on the outer surface of the MOFs nanoreactor and the transition metal nickel is loaded on the inner surface of the MOFs nanoreactor by adsorption-impregnation, thereby forming a MOFs nanoreactor loaded with dual catalysts; S300, mixing a polyolefin matrix: uniformly mixing the polyolefin matrix with additives and fillers to form a polyolefin matrix mixture; S400, introducing a dynamic thiol-ene click reaction: mixing thiol and olefin monomers, adding the mixture to a polyolefin matrix mixture, and uniformly dispersing the thiol and olefin monomers in the polyolefin matrix by stirring to form a mixture containing a dynamic thiol-ene click reaction system; S500, reactive extrusion: extruding and mixing a mixture containing a MOFs nanoreactor and a dynamic thiol-ene click reaction system through the third section of a twin-screw extruder. During the extrusion process, the components are fully mixed and uniformly mixed through the shearing and mixing action of the screw. Meanwhile, the dynamic thiol-ene click reaction reacts during the extrusion process to form a pre-crosslinked network structure. S600, microwave curing: the extruded mixture is cured, and under the action of microwaves, a local temperature gradient is induced in the material to form a flame retardant gradient structure; S700, post-processing: performing post-processing operations of cooling and cutting the cured composite material to obtain a final catalytic carbonization flame-retardant polyolefin nanocomposite material.
5. The catalytic carbonization flame-retardant polyolefin nanocomposite material according to claim 4, characterized in that: The temperature of the first section of the S100 twin-screw extruder is 80-120°C. During the synthesis of ZIF-8 in a polyolefin matrix, an ultrasonic-assisted micro-reaction technology with a frequency of 40kHz and a power density of 0.5W / cm² is turned on.
6. The catalytic carbonization flame-retardant polyolefin nanocomposite material according to claim 4, characterized in that: The temperature of the second section of the S200 twin-screw extruder is 150-180° C., and an aluminum hypophosphite / nickel salt mixed solution is injected to achieve selective loading by utilizing the molecular sieve effect of the MOFs pores. By adjusting the pH value of the system to 5.5-6.0, nickel ions are preferentially adsorbed on the inner surface of MOFs, and aluminum hypophosphite is distributed on the outer surface, forming a gradient distribution structure.
7. The catalytic carbonization flame-retardant polyolefin nanocomposite material according to claim 4, characterized in that: The temperature of the third section of the S500 twin-screw extruder is 200-220°C, thiol and olefin monomers are introduced, and the alternating distribution of high shear zone and low shear zone is achieved by setting the kneading block angle to 45° and the gap to 0.5mm, and the crosslinking degree is controlled at 15-25%.
8. The catalytic carbonization flame-retardant polyolefin nanocomposite material according to claim 4, characterized in that: The S600 microwave has a frequency of 2.45 GHz, a power density of 2-3 W / g, and a treatment time of 1-5 minutes.
9. An application of a catalytic carbonization flame-retardant polyolefin nanocomposite material, which is applicable to the application of a catalytic carbonization flame-retardant polyolefin nanocomposite material as described in any one of claims 1 to 3 in the preparation of flame-retardant wires and cables, flame-retardant building materials and flame-retardant plastic products.
Citation Information
Cited By
Core-shell structure flame retardant containing phosphorus in different oxidation states prepared by click chemistry and application of core-shell structure flame retardant
CN121873437A